A survey of rice insect pests in Nigeria - Alam, M.S. (Informa UK Limited, 1992)
survey of rice insect pests conducted during 1983–87 in Nigeria revealed 70 species of pests, 14 parasitoids and two predators. Both incidence and severity of pests varied considerably across different climatic zones and rice agro‐ecosystems. Thirteen Insects were classified as major pests. They are: stalk‐eyed fly. Diopsis longicornis Macquart; lepidopterous stem borers. Mallarpha separatella Rag., Chllo zacconiusBlesz, Sesamia spp.; African gall midge, Orseolia oryzivoraH&G;armyworm, Spodoptera spp.; leaf folder, Marasmia trapezalls Guenée; grain‐sucking bugs. Asparvia armlgera Fab., Stenocoris spp.; case worm, Nymphula stagnalis Zell; lady bird beetle, Epilachna similis Thunb.; whorl maggot, Hydrellia prosternalis R&D; and termites. The brown plant hopper, Nilaparvata maeander Fennah, and whitefly, Aleurocybotus indicus D&S are potentially serious pests. The insect pest situation will probably change in Nigeria as the use of modern inputs increases, based on experience In Asia.